2012
DOI: 10.1073/pnas.1204865109
|View full text |Cite
|
Sign up to set email alerts
|

Large enantiomeric excesses in primitive meteorites and the diverse effects of water in cosmochemical evolution

Abstract: Carbonaceous chondrites are meteoritic fragments of asteroids that avoided the geological reprocessing of larger planets and allow laboratory probing of early solar-nebula materials. Among these, Renazzo-type (CR) chondrites found in Antarctica appear remarkably pristine and are distinguished by abundant organic materials and water-soluble molecules such as amino acids and ammonia. We present a comprehensive analysis of the organic composition of selected CR meteorites of different petrographic classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
160
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(173 citation statements)
references
References 37 publications
9
160
3
1
Order By: Relevance
“…Racemic mixtures are equated with pristine/uncontaminated abiotic samples when discussing meteoritic compounds. However, some meteoritic amino acids that are rare on Earth, i.e., they are not constituents of proteins and therefore less likely to be contaminants, have been confirmed to contain L enantiomer excesses (EE) (3,12,13). The origins of such excesses are unknown.…”
mentioning
confidence: 99%
“…Racemic mixtures are equated with pristine/uncontaminated abiotic samples when discussing meteoritic compounds. However, some meteoritic amino acids that are rare on Earth, i.e., they are not constituents of proteins and therefore less likely to be contaminants, have been confirmed to contain L enantiomer excesses (EE) (3,12,13). The origins of such excesses are unknown.…”
mentioning
confidence: 99%
“…The discovery of a large number of meteorites since 1969 has provided new opportunities to search for organic compounds in CM-type carbonaceous chondrites (Pizzarello et al 2001;Glavin et al 2006;Pizzarello and Shock 2010) as well as in Renazzo-type (CR) chondrites found in Antarctica with natal enantiomeric excesses of up to 60 % (Pizzarello et al 2012). …”
Section: Meteoritesmentioning
confidence: 99%
“…We address here Elsila et al's criticism (1) regarding our recent article (2) and, in particular, their claim that our chiral analyses of isoleucine (ile)/alloisoleucine (allo) diastereomers were possibly flawed. We first remind the authors that these compounds' enantiomeric excesses (ee) were already studied recently, validated by compound-specific 13 C analyses (3), and their unambiguous meteoritic indigeneity remains the foundation for our new, expanded analyses (2).…”
mentioning
confidence: 99%
“…. is not acidic and subject to racemization" (2). Indeed, α-carbon epimerization cannot remove ile/allo natal ee, but Elsila et al (1) fail to mention that it can decrease larger ee and increase lesser ee if L-ile ee ≠ D-allo ee.…”
mentioning
confidence: 99%
See 1 more Smart Citation